Silicon Dioxide (SiO2) Is the Most Important Component of Spots on the Inner Surface of Mactra veneriformis Shells - He, Cheng; Zhang, Baolu; Wei, Lei; Yu, Wenchao; Jiang, Qiuyun; Wang, Xiaona; Guo, Wen; Wang, Xiaotong (Frontiers in Marine Science, 2019)
Yellow-brown spots are often observed on the inner shell surface of the clam Mactra veneriformis sampled in Binhai New Area, Lijin County, Shandong Province, China, negatively impacting its commercial value. In this study, SEM-EDS, X-ray diffraction (X-rd), laser Raman spectrum, and Fourier infrared spectrum scanning (FT-IR) were used to detect and analyze the composition of spots on the inner shell surface of these clams. Compared with shells without spots, the shells with spots showed significant differences in their silicon contents but no differences in the content of other basic elements; Laser Raman spectroscopy and X- rd examination revealed that, in addition to calcium carbonate particles, there were traces of silica bonds; after the removal of calcium carbonate by using hydrochloric acid, the spectral trend of particles was similar to that of sea sand, which was consistent with the spectral characteristics of SiO2. Therefore, the spots on the inner shell surface of M. veneriformis are sea sand. These are likely to result from the increased sand content in seawater in the Yellow River Delta, whereby the grains of sand have fallen into the gap between the mantle and shell; thus, the sand becomes encased in the shells as they grow.